The House of the Vampire - Viereck, George Sylvester, 1884-1962 (Salt Lake City, UT : Project Gutenberg, 2005)
"The House of the Vampire" by George Sylvester Viereck is a novel written in the early 20th century. The story unfolds in a vibrant New York City and centers around Reginald Clarke, a charismatic and enigmatic writer whose influence extends beyond mere words. As he captivates those around him with his charm and artistry, he inadvertently casts a shadow on the lives of aspiring artists like Ernest Fielding, raising themes of creative genius, obsession, and the fine line between inspiration and parasitism. At the start of the novel, the reader is introduced to Reginald Clarke, whose presence at a crowded restaurant draws both admiration and distress from those who recognize him. Clarke's past connection with Ethel Brandenbourg, a painter whose work has suffered since their separation, highlights the impact he has on others. In a gripping conversation, Clarke reminisces about his psychological power and its effects, while Ernest Fielding, who idolizes Clarke and strives for artistic success, navigates his own feelings of admiration mixed with anxiety. Ernest's experiences foreshadow a deepening intrigue as he becomes ensnared in the vortex of Clarke's genius, which threatens to absorb his own creative spirit. (This is an automatically generated summary.)
Release date is 2005-11-23
E-text prepared by Suzanne Lybarger, Janet Blenkinship, Brian Janes, and the Project Gutenberg Online Distributed Proofreading Team (https://www.pgdp.net/)
Keywords: Horror tales; Vampires -- Fiction